From Identification to Intelligence: An Assessment of the Suitability of Forensic DNA Phenotyping Service Providers for Use in Australian Law Enforcement Casework - Atwood, Lauren; Raymond, Jennifer; Sears, Alison; Bell, Michael; Daniel, Runa (Frontiers in Genetics, 2021)
Forensic DNA Phenotyping (FDP) is an established but evolving field of DNA testing. It provides intelligence regarding the appearance (externally visible characteristics), biogeographical ancestry and age of an unknown donor and, although not necessarily a requirement for its casework application, has been previously used as a method of last resort in New South Wales (NSW) Police Force investigations. FDP can further assist law enforcement agencies by re-prioritising an existing pool of suspects or generating a new pool of suspects. In recent years, this capability has become ubiquitous with a wide range of service providers offering their expertise to law enforcement and the public. With the increase in the number of providers offering FDP and its potential to direct and target law enforcement resources, a thorough assessment of the applicability of these services was undertaken. Six service providers of FDP were assessed for suitability for New South Wales Police Force casework based on prediction accuracy, clarity of reporting, limitations of testing, cost and turnaround times. From these assessment criteria, a service provider for the prediction of biogeographic ancestry, hair and eye colour was deemed suitable for use in NSW Police Force casework. Importantly, the study highlighted the need for standardisation of terminology and reporting in this evolving field, and the requirement for interpretation by biologists with specialist expertise to translate the scientific data to intelligence for police investigators.